BILINGUALISM TELEVISION UKRAINE AS A RESULT SYSTEM LANGUAGE RUSSIAN AGGRESSION - Dymnich, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This article attempts to analyze language media processes in Ukraine, to isolate the effects of systemic language Russian aggression and clarify the impact of bilingual television programs to pro cess national identity of the person.